Analysis of the p-11B Fusion Scenario with Compensation of the Transfer of Kinetic Energy of Protons and Alpha Particles to the Gas Medium by the Electric Field. (28th June 2022) - Shmatov, Mikhail L.
Abstract : The energy balance of the p- 11 B fusion scenario with compensation of the transfer of kinetic energy of protons and alpha particles to the gas medium by the electric field is considered. It is shown that such scenario cannot provide the use of p- 11 B fusion reaction for power production due to the very low ratio of the energy release of the fusion reaction to the energy necessary for compensation. The upper boundary of this ratio is about 2 × 10 − 3 .